2007
DOI: 10.1038/ng2043
|View full text |Cite
|
Sign up to set email alerts
|

A variant in CDKAL1 influences insulin response and risk of type 2 diabetes

Abstract: A variant in CDKAL1 influences insulin response and risk of type 2 diabetes Steinthorsdottir, V.; Thorleifsson, G.; Reynisdottir, I.; Benediktsson, R.; Jonsdottir, T.; Walters, G.B.; Styrkarsdottir, U.; Gretarsdottir, S.; Emilsson, V.; Ghosh, S.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

39
689
11
9

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 940 publications
(748 citation statements)
references
References 25 publications
39
689
11
9
Order By: Relevance
“…Especially, they were all located within CDKAL1 gene except for an intergenic variant of rs5015480 near HHEX gene. The association of the CDKAL1 gene concurred with the results from previous studies with American, 1 British, 5 French, 3 Danish, 4 Finnish, 2 Swedish, 1 Icelandic, 4 Korean, 9 Japanese, 10 and Chinese [11][12][13] populations. The significantly associated variants of the gene in the current study were specifically corresponding to those found in previous studies of Horikawa et al 14 and Wu et al 11 for rs7756992 and Zeggini et al 5 and Wu et al 11 for rs9465871 and rs10946398, respectively.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Especially, they were all located within CDKAL1 gene except for an intergenic variant of rs5015480 near HHEX gene. The association of the CDKAL1 gene concurred with the results from previous studies with American, 1 British, 5 French, 3 Danish, 4 Finnish, 2 Swedish, 1 Icelandic, 4 Korean, 9 Japanese, 10 and Chinese [11][12][13] populations. The significantly associated variants of the gene in the current study were specifically corresponding to those found in previous studies of Horikawa et al 14 and Wu et al 11 for rs7756992 and Zeggini et al 5 and Wu et al 11 for rs9465871 and rs10946398, respectively.…”
Section: Discussionsupporting
confidence: 89%
“…The heterogeneity by gender was a novel finding for T2DM. The larger effect of the CDKAL1 in females concurred with the study of Steinthorsdottir et al, 4 showing a larger association of rs7756992 with insulin secretion in females (Po0.00001) than in males (Po0.001). The differential effect would lead to a deflated association by adding males in the association analysis.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The pancreatic β cells were stimulated to secrete insulin to regulate the homoeostasis of the blood glucose by the postprandial high levels of blood glucose [5]. Until now, hundreds of genetic variations related with T2D or glucose/insulin have been identified by GWAS (Genome Wide Association Studies) [6-9]. Most T2D risk genes identified in GWAS performs the biological processes which affect the number or function of the pancreatic β cells, emphasizing the important effect of β cells in the occurrence and development of T2D [10].…”
Section: Introductionmentioning
confidence: 99%
“…La cartographie détaillée et les études fonctionnelles sauront, on l'espère, distinguer lequel des deux gènes est en cause. Parallèlement à nos travaux, quatre autres équipes concurrentes, qui participent à cette course internationale, viennent de publier des études semblables qui confirment ces deux associations et en mettent en évidence six autres [5][6][7][8]. Ensemble, ces nouvelles associations, additionnées à celles qui étaient déjà détermination simultanée du génotype de centaines de milliers de polymorphismes d'un nucléotide (SNP) à haut débit.…”
unclassified